PENGARUH PENGGUNAAN RAGI ALAMI DARI SAYURAN LOKAL TERHADAP UMUR SIMPAN ROTI TAWAR OPEN TOP - Santoni, Jaja Kurnia (Jurnal Pendidikan Teknik dan Vokasional, 2021)
This research is aimed (1) to develop natural refreshed starter based on local vegetables (2) to learn its implementation on open top toast bread (3) to observe the quality differences of open top toast bread using chinese cabbage and carrot refreshed starter, based on organoleptic aspects, physical characteristic and shelf life. This research was conducted at PT Saf Indonusa Baking Center Laboratorium, Jakarta, on November - December 2016. Experimental research was done for this research. Friedman Statistic Test and Tukey’s analysis results, showed the differences of open top toast bread final quality, using 10%, 20% and 30% chinese cabbage or carrot refreshed starter. The best finding was shown by subject’s outer color using 20% of chinese cabbage refreshed starter. Shelf life analysis showed that mold was detected on subject with 20% chinese cabbage and carrot refreshed starter on day 2; while for softness aspect of crumbs best results was showed on subject using 20% chinese cabbage and carrot based refreshed starter on day 2. Keywords: toast bread quality, natural starter, local vegetable